Organizational structure and technological investment - Inés Macho-Stadler; Noriaki Matsushima; Ryusuke Shinohara (Osaka University, Institute of Social and Economic Research (ISER), 2019)
We analyze firms' decisions to adopt a vertical integrated or decentralized structure taking into account the characteristics of both the final good competition and the R&D process. We consider two vertical chains, where R&D is conducted by upstream sectors. R&D investment determines the production costs of the downstream sector and has spillovers on the rivals' costs. In a general setup, we show that equilibrium organizational structure depends on whether the situation considered belongs to one of four possible cases and we study how final good market competition, spillover, and incentives in innovation interact to determine the optimal vertical structure.
Keywords: L22; L13; O32; C72; 330; R&D; Vertical separation; Market structure; Spillover; R&D; Vertical separation; Market structure; Spillover